La 'scoperta' dei disoccupati Alle origini dell'indagine statistica sulla disoccupazione nell'Italia liberale (1893-1915) - Alberti, Manfredi (Premio Tesi di Dottorato, 2013)
In Italy, the problem of involuntary unemployment, although known to the working classes and public authorities at least since the age of the Risorgimento, only became the subject of specific attention at the end of the nineteenth century. It is only at that time that a political and economic debate arises on the lack of work and on the means to contrast it, on the scenario of the end-of-century depression and simultaneously to the development of the workers and peasants movements. Those years saw the foundations for the experimentation of a pioneering statistical measurement of the phenomenon, which, however, would only come to light during the Giolittian age, in a political context more open to the demands of work. This research reconstructs for the first time the "focus" of a typical problem of capitalism, which also proves itself of great interest central also in the contemporary debate.